Impact of industrial agglomeration on Chinas residents' consumption - Zhang, Suhua; Bani, Yasmin; Selamat, Aslam Izah; Abdul Ghani, Judhiana (Multidisciplinary Digital Publishing Institute, 2022)
Residents’ consumption is a good indicator of people’s livelihoods and one of the motivations driving economic growth. There are many studies on the influencing factors of residents’ consumption; however, few have studied the effects of industrial agglomeration on residents’ consumption, and even fewer have studied the spatial correlation of residents’ consumption. The goal of this paper is to research the impact of China’s manufacturing industrial agglomeration on residents’ consumption from a spatial perspective. Using data on China’s 31 provinces from 2003 to 2019 and the spatial Durbin model, our results show that the manufacturing industrial agglomeration and residents’ consumption present an inverted “U-shape” relationship and that different regions show different effects. Industrial agglomeration in the eastern region is relatively high and has a restraining effect on residents’ consumption, while industrial agglomeration in the central and western regions is at an early stage and promotes residents’ consumption. Therefore, different regions should adopt different industrial agglomeration policies.